Comparison of FGF-8, FGF-10, FGF-Receptor 2, Androgen Receptor, Estrogen Receptor-A and SS in Healthy and Hypospadiac Children - Emaratpardaz N; Turkyilmaz Z; Karabulut R; Dayanir D; Kaya C; Sert AAE; Arkan G; Ucaner FA; Kapisiz A; Eryilmaz S; Atan A; Sonmez K (Balkan Journal of Medical Genetics, 2024)
In this study, we aimed to investigate the levels of Fibroblast Growth Factor-8 (FGF-8), FGF-10, FGF-Receptor-2 (FGFR-2), Androgen receptor (AR), Estrogen receptor alpha and beta (ER-α and ER-β) in the foreskins of children with and without hypospadias.